Transforming corrections: humanistic approaches to corrections and offender treatment - Polizzi, David; Braswell, Michael; Draper, Matthew (Carolina Academic Press, 2014)
Foreword / Hans Toch -- Introduction / David Polizzi and Michael Braswell -- A phenomenological approach to criminology / Christopher M. Aanstoos -- Phenomenological and existential approaches to crime and corrections / Kenneth Adams and Hayden Smith -- Offender objectification : implications for social change / John S. Ryals -- Dialogue : a unique perspective for correctional counseling / Matthew R. Draper, Mark S. Green, and Ginger Faulkner -- Transforming corrections through psychological jurisprudence : a preliminary review and critique of theory / Bruce Arrigo -- Mutual respect and effective prison management / Terry A. Kupers -- Civility in prisons : a radical proposal / Catherine A. Jenks and John Randolph Fuller -- Varieties of restorative justice : therapeutic interventions in context / Lana McDowell and John Whitehead -- Correctional treatment and the human spirit : the context of relationship / Michael Braswell and Kristin Wells -- Psycho-spiritual roots of adolescent violence : the importance of rites of passage / Drake Spaeth -- Developing therapeutic trust with court-ordered clients / David Polizzi -- Epilogue : toward a more humanistic future in corrections / David Polizzi